2015
DOI: 10.1111/jsm.13067
|View full text |Cite
|
Sign up to set email alerts
|

Penile Prosthesis Implantation in Patients with a History of Total Phallic Construction

Abstract: Introduction Outcomes following penile prosthesis implantation in patients with a history of total phallic construction are not well described. Aim The aim of this study was to evaluate outcomes following neophallus penile prosthesis placement. Methods Retrospective review penile prosthesis placement in patients with prior total phallic construction. GORE-TEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The authors assert that the neotunica aids in alignment of the neophallus and helps secure the proximal cylinder. They also claim that GORE-TEX ® provides adequate stretch for the cylinder when inflated (11). Other groups have reported that encasing the entire cylinder in graft material may result in higher rates of mechanical failure and cylinder aneurysm due to excess constraint on the cylinder during inflation (14,25).…”
Section: Proximal Fixation Of the Cylindermentioning
confidence: 97%
See 4 more Smart Citations
“…The authors assert that the neotunica aids in alignment of the neophallus and helps secure the proximal cylinder. They also claim that GORE-TEX ® provides adequate stretch for the cylinder when inflated (11). Other groups have reported that encasing the entire cylinder in graft material may result in higher rates of mechanical failure and cylinder aneurysm due to excess constraint on the cylinder during inflation (14,25).…”
Section: Proximal Fixation Of the Cylindermentioning
confidence: 97%
“…Though this remains the most common technique of achieving rigidity in the neophallus, the ideal method of accomplishing this goal remains controversial. With reported modern complication rates ranging from 23-70%, there is clearly room for improvement in this realm (9)(10)(11)(12)(13)(14). With the growing population of patients who desire these procedures, ongoing development and refinement in techniques continues by leaders in the field.…”
Section: Review Articlementioning
confidence: 99%
See 3 more Smart Citations